2018
DOI: 10.21608/ejh.2018.3019.1001
|View full text |Cite
|
Sign up to set email alerts
|

A histological and immunohistochemical study on the possible protective role of silymarin on cerebellar cortex neurotoxicity of lactating albino rats and their pups induced by gibberellic acid during late pregnancy and early postnatal period

Abstract: Introduction: Plant growth regulators (PGRs), especially gibberellic acid (GA3), are used to increase the production and the availability of the plants all the year. Silymarin has recently been reported to be a neuroprotective agent against much neurologic diseases. Aim: To investigate the effects of GA3 treatment during late pregnancy and early postnatal periods on the rat's cerebellar cortex of lactating mothers and their pups. Besides, to detect the possible protective-role of silymarin. Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Their cell bodies (soma) were the immense soma in the cerebellum and displayed a discernible and unique morphology. This finding agrees with birds' mammalian and nonmammalian cerebellum (Fahad & Mitchel, 2007; Mohamed & Mohamed, 2018; Roshdy & Derbalah, 2021). The Purkinje cells were arranged in a solitary row.…”
Section: Discussionsupporting
confidence: 85%
“…Their cell bodies (soma) were the immense soma in the cerebellum and displayed a discernible and unique morphology. This finding agrees with birds' mammalian and nonmammalian cerebellum (Fahad & Mitchel, 2007; Mohamed & Mohamed, 2018; Roshdy & Derbalah, 2021). The Purkinje cells were arranged in a solitary row.…”
Section: Discussionsupporting
confidence: 85%
“…The histological examination of the cerebellum, in the control group revealed no anomalies or alterations in histology as observed by 29 implying that these animals were in good health and that the experiment was carried out properly.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, the present study was established to assess the potential hazard of tartrazine on the cortex of the cerebellum in the adult albino rat as well as the potential safeguarding role of riboflavin. The histological examination of the cerebellum, in the control group revealed no anomalies or alterations in histology as observed by 29 implying that these animals were in good health and that the experiment was carried out properly.…”
Section: Discussionmentioning
confidence: 72%
“…Mohamed and Mohamed [2018] suggested that the vacuolation happened due to cell injury which was accompanied by increased production of ROS and lipid peroxidation that altered cell membrane permeability and oxidative destruction of cells. Ultrastructurally, the observed nuclear changes were explained by Ali et al [2018] and Mohamed and Mohamed [2018]. They stated that the condensed nuclear chromatin might be an outcome of condensation and dissolution of chromatin of dying neurons.…”
Section: Dzn Induced Neurodegenerative Changes In the Purkinje And Gr...mentioning
confidence: 99%
“…The cerebellum is susceptible to environmental and developmental hazardous factors because the Purkinje cell's maturity and the granular cell development occurs mainly postnatally and they are important highly sensitive parameters for the toxic substance [Nassar, 2009;Mohamed and Mohamed, 2018].…”
Section: Dzn Induced Neurodegenerative Changes In the Purkinje And Gr...mentioning
confidence: 99%